Respostas
respondido por:
1
-2a² - 6a + 12ab - 12b para a = 1 e b = 2
-2(1)² - 6(1) + 12(1)(2) - 12(2)
-2.1 - 6 + 24 - 24
-2 - 6 = -8
Resposta: - 8
Espero ter ajudado.
-2(1)² - 6(1) + 12(1)(2) - 12(2)
-2.1 - 6 + 24 - 24
-2 - 6 = -8
Resposta: - 8
Espero ter ajudado.
ProfRafael:
Obrigado!
respondido por:
1
a = 1 e b = 2
-2(1)² - 6(1) + 12(1)(2) - 12(2)
-2.1 - 6 + 24 - 24
-2 - 6 = -8
resposta 8
-2(1)² - 6(1) + 12(1)(2) - 12(2)
-2.1 - 6 + 24 - 24
-2 - 6 = -8
resposta 8
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás